Enhancing the physiological characteristics of chimeric antigen receptor natural killer cells by synthetic biology - Ji, Shuochao; Jin, Cheng; Cui, Xinjiang (Frontiers in Immunology, 2025)
Chimeric antigen receptor natural Killer (CAR-NK) cells therapy represents a next-generation immunotherapeutic approach following CAR-T cells therapy, offering inherent “off-the-shelf” compatibility and mitigated off-tumor toxicity. Despite these advantages, clinical translation remains constrained by poor in vivo persistence and functional exhaustion in immunosuppressive tumor microenvironments (TME). This review examines recent advancements in synthetic biology aimed at enhancing the physiological characteristics of CAR-NK cells. By delineating the synergy between NK cells and synthetic biology toolkits, this work provides a roadmap for developing next-generation CAR-NK therapies capable of addressing solid tumor challenges while maintaining favorable safety profiles.